Influence of stabilizers on composition, sensory properties and microbial load of yoghurt made from zebu milk (2015)
Yoghurt is a popular dairy product with wide consumer acceptance around the world. The use of stabilizers to improve the sensory attributes of yoghurt and enhance profitability in yoghurt-making has become common practice. In this study, the effects of Corn Starch (CS), Milk Powder (MP) and Baobab Fruit pulp (BF) as stabilizers in the yoghurt mix was evaluated. Raw zebu milk was homogenized, pasteurized at 75°C for 20 min and incubated at 43°C for 6-8 h until a gel was formed. Milk powder was added to the milk prior to homogenization while corn starch and baobab fruit pulp were added to yoghurt after incubation. Chemical composition, sensory attributes and microbial load of yoghurts formed were determined. Results show that the use of different stabilizers influenced the chemical composition, sensory attributes and microbial load of the yoghurt formed. Total solids varied from 14.34-16.70%, protein from 3.57-5.50% and fat from 4.33-5.30% in the yoghurts. Total solids increased with addition of stabilizers while protein and fat content increased only in MP and reduced in CS. The use of BF did not significantly alter the protein and fat content of yoghurts. With the exception of BF, addition of stabilizers generally improved sensory attributes and overall acceptability of yoghurt. Sensory scores shows that acceptance of the yoghurts was in the order, MP>CS>control>BF. The microbial load of the yoghurt increased with the addition of stabilizers. Coliform, fungal and total viable counts varied from 0.1-2.4x10(2), 0.1-1.8x10(2) and 0.2-2.5x10(3), respectively and was in the order, MP>BF>CS>control. While, addition of stabilizers to yoghurt may be desirable, high hygienic standards must be adopted in the production of stabilizers in order to avoid microbial contamination of yoghurt.